2010
DOI: 10.1186/1472-6882-10-73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypericum Perforatum, in a rodent model of periodontitis

Abstract: BackgroundHypericum perforatum is a medicinal plant species containing many polyphenolic compounds, namely flavonoids and phenolic acids. In this study we evaluate the effect of Hypericum perforatum in animal model of periodontitis.MethodsPeriodontitis was induced in adult male Sprague-Dawley rats by placing a nylon thread ligature around the lower 1st molars. Hypericum perforatum was administered at the dose of 2 mg/kg os, daily for eight days. At day 8, the gingivomucosal tissue encircling the mandibular fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 24 publications
5
41
0
1
Order By: Relevance
“…Due to its SSRIs mechanism of action, Hypericum perforatum could be attributed to the significant improvements in serum levels of T4, TSH in irradiated rats. Besides its anti-stressful [47] and anti-inflammatory properties [48], Hypericum perforatum has a powerful antioxidant activity by normalizing serum total antioxidant capacity as well as Malondialdehyde level [49,50]. Also Hypericum perforatum had the ability for protecting neurons from nitric oxide (NO) oxidative stress-induced cell death which occurs in glucose deprivation (GD)-induced neurotoxicity [51].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its SSRIs mechanism of action, Hypericum perforatum could be attributed to the significant improvements in serum levels of T4, TSH in irradiated rats. Besides its anti-stressful [47] and anti-inflammatory properties [48], Hypericum perforatum has a powerful antioxidant activity by normalizing serum total antioxidant capacity as well as Malondialdehyde level [49,50]. Also Hypericum perforatum had the ability for protecting neurons from nitric oxide (NO) oxidative stress-induced cell death which occurs in glucose deprivation (GD)-induced neurotoxicity [51].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism mentioned in previous studies was NF-kB. HP signifi cantly reduces the NF-kB translocation (30,31). Morever, it was demonstrated that HP treatment also inhibits the IkB-α degredation.…”
Section: A C B Dmentioning
confidence: 91%
“…Morever, it was demonstrated that HP treatment also inhibits the IkB-α degredation. NF-kb plays a central role in the regulation of many genes responsible for the cytokines including TNF-α and IL-1β which has role in propagating the extension of a local and systemic infl ammatory process (30,31). However the exact mechanisms by which HP supress NF-kB activation are not known exactly.…”
Section: A C B Dmentioning
confidence: 99%
“…It is reported in the literature to have antispasmodic, sedative, antiseptic, and antidepressive effects as well as wound-healing effects (10,11). In addition, it is known to be effective against bacteria, viruses, inflammation, and pain (11,12).…”
Section: Introductionmentioning
confidence: 99%